Evaluation and Influencing Factors of Coupling Coordination of “Production–Living–Ecological” Functions Based on Grid Scale: Empirical Experience of Karst Beibu Gulf in Southwest Guangxi, China - Ting Feng; Dong Wu; Xiaodong Yu; Meilin Zhang; Renling Dong; Sihan Chen (Land)
Territorial space (TS) is multifunctional, and exploring the relationships between functions and their influencing factors is key to achieving sustainable development of territorial space. However, existing research mostly focuses on the exploration of administrative units, while the exploration of grid units needs to be improved. This paper takes the Beibu Gulf Economic Zone (BGEZ) in Guangxi as the research object, evaluates the “Production–Living–Ecological” Functions (PLEFs) of territorial space using the land category scoring method and summarizes the evolution characteristics of its spatial pattern. It analyzes the dominant and combined functions of territorial space using the revealed comparative advantage index, explores the relationships between various functions by introducing a coupling coordination degree model, and comprehensively uses Geodetector and Geographically and Temporally Weighted Regression (GTWR) models to analyze the spatiotemporal heterogeneity of influencing factors on the coupling coordination degree of functions. The results indicate that at the grid scale (1) regional territorial space is dominated by ecological space, followed by production space, with living space accounting for the smallest proportion. Production space and ecological space has decreased, while living space has increased, with production and ecological spaces mostly flowing into living space. (2) The spatial distribution of production and ecological functions is relatively homogeneous, while the spatial differentiation of living functions is most significant. The grid can be divided into three function-dominant types and six function-combination types. (3) Living function is primarily disordered with production and ecological functions, while production–ecological function is mainly coordinated. (4) Policy regulation is a key factor affecting the degree of functional coordination, and the degree and scope of influence of each factor show significant spatiotemporal heterogeneity. This study reveals the functional relationships and the mechanisms of temporal and spatial evolution of TS at the grid scale, providing a scientific basis for the efficient and sustainable use of TS.